2021
DOI: 10.1111/acel.13323
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genetic analyses revealed novel human longevity loci and reduced risks of multiple diseases in a cohort study of 15,651 Chinese individuals

Abstract: There is growing interest in studying the genetic contributions to longevity, but limited relevant genes have been identified. In this study, we performed a genetic association study of longevity in a total of 15,651 Chinese individuals. Novel longevity loci, BMPER (rs17169634; p = 7.91 × 10−15) and TMEM43/XPC (rs1043943; p = 3.59 × 10−8), were identified in a case–control analysis of 11,045 individuals. BRAF (rs1267601; p = 8.33 × 10−15) and BMPER (rs17169634; p = 1.45 × 10−10) were significantly associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 78 publications
(112 reference statements)
0
39
0
1
Order By: Relevance
“…Furthermore, sex differences for longevity are recently more reported (Mitchell et al, 2016). For instance, a recent study found sex-specific single nucleotide polymorphism for human longevity genes, including the most common identified longevity loci TOMM40 and APOE (Liu et al, 2021). Thus, future studies should attempt to parse the data in a sex-specific manner to more accurately determine these gender-specific signatures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sex differences for longevity are recently more reported (Mitchell et al, 2016). For instance, a recent study found sex-specific single nucleotide polymorphism for human longevity genes, including the most common identified longevity loci TOMM40 and APOE (Liu et al, 2021). Thus, future studies should attempt to parse the data in a sex-specific manner to more accurately determine these gender-specific signatures.…”
Section: Discussionmentioning
confidence: 99%
“…These candidate SNPs were selected based on previously published associations with longevity, chronic diseases, and health indicators. Further details on the genotyping platform, sample filtering, and quality control can be found in our published work (Zeng et al, 2016 ; Liu et al, 2021 ). Consistent with prior studies, we determined APOE genotypes using the two SNPs: rs429358 and rs7412 (Zhu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic associated signals of TOMM40 in AD have traditionally been dismissed as surrogate signals of APOE [46,47]; however, this viewpoint has gradually shifted to consider TOMM40 as an independent contributor to AD risk and healthy aging. For example, genetic variants in TOMM40 have been consistently linked to longevity and healthy aging [48][49][50][51]. The SNP rs2075650 located in intron 2 of TOMM40 has been considered a proxy of the SNP rs429358 that defines the ε4 allele of APOE [29].…”
Section: Discussionmentioning
confidence: 99%